Simulations of membrane‐bound diglycosylated human prion protein reveal potential protective mechanisms against misfolding. Issue 1 (22nd May 2017) - Cheng, Chin Jung; Koldsø, Heidi; Van der Kamp, Marc W.; Schiøtt, Birgit; Daggett, Valerie
Abstract : Abstract: Prion diseases are associated with the misfolding of the prion protein (PrP) from its normal cellular form (PrP C ) to its infectious scrapie form (PrP S c ). Post‐translational modifications in PrP in vivo can play an important role in modulating the process of misfolding. To gain more insight into the effects of post‐translational modifications in PrP structure and dynamics and to test the hypothesis that such modifications can interact with the protein, we have performed molecular dynamics simulations of diglycosylated human PrP C bound to a lipid bilayer via a glycophosphatidylinositol anchor. Multiple simulations were performed at three different pH ranges to explore pH effects on structure and dynamics. In contrast to simulations of protein‐only PrP C, no large effects were observed upon lowering the pH of the system. The protein tilted toward the membrane surface in all of the simulations and the putative PrP S c oligomerization sites became inaccessible, thereby offering a possible protective mechanism against PrP S c ‐induced misfolding of PrP C . Abstract : Diglycosylated human prion protein PrP C bound to a lipid bilayer did not misfold upon lowering the pH in molecular dynamics simulations, in contrast to the non‐glycosylated protein in water, but the protein tilted toward the membrane surface and putative sites for misfolding and oligomerization became inaccessible, thereby offering a possible protective mechanism against misfolding.